Effective Cost Cutting in Asia Practical Modern Approach for Managers and Engineers in Industry to Achieve Profit Growth - Zuerl, Karlheinz (Cham : Springer International Publishing : Imprint: Springer, 2022)
The days of cheap raw materials and energy sources are gone. Suppliers will demand price increases due to the rising costs of energy and materials. This book describes how your purchasing department is able to gain (more) profit for your company and includes new ideas for successful purchasing and supplier development in Asia. The author discusses how to reduce costs in productive (BOM) and non-productive materials (NPMs) and how to calculate product and tool costs. As well, the book shows ways to negotiate your results with your suppliers in Asia and build an effective system of supplier relationship management.
Chapter 1. GTEC Service, Consulting and Training -- Chapter 2. The Purchasing Manager's Challenges in Asia -- Chapter 3. Asian Supplier Productivity Diagnosis -- Chapter 4. Supplier Development in Asia in 5 Steps -- Chapter 5. The Purchasing Organization of The Future -- Chapter 6. Cost Break Down and Cost Structure Analysis -- Chapter 7. Negotiations with Asian Suppliers -- Chapter 8. Cultural Diversity in Asia-Pacific.
Keywords: Business; Asia; Diversity in the workplace; Strategic planning; Leadership; Business enterprises-Finance.; Production management; Business logistics; Asian Business; Cross-Cultural Management; Business Strategy and Leadership; Corporate Finance; Operations Management; Supply Chain Management